KONDOMISASI BUAH KAKAO (Theobroma cacao Linnaeus) DI DESA MATANG ARA JAWA, KECAMATAN MANYAK PAYED, KABUPATEN ACEH TAMIANG - Maria Heviyanti; Fiddini Alham; Astri Afriani (LPPM dan PM Universitas Samudra, 2020)
Helopeltis spp is one of the major pests in cocoa plantation that caused loss of young pods and damage to branches and twigs. Farmers usually used chemical insecticide to control the pests that can cause pesticide resistance, resurgence, and secondary pest outbreak. Integrated pest management is the alternative pest control method as a long term prevention of pests with the combination of techniques. Sarungisasi (condomization) is the prevention of pests attack in cocoa pod. Community service program is the implementation of science, technology, and culture of art to the community. Partners of the community service program are Datok penghulu, farmers, and extension agent in Matang Ara Jawa District. This program was designed as a response to the problems of low cocoa pod production due to cacao sucking-pod bugs that cause young pod become rotten and fall easily. Through condomization cacao pod will suppress the pod sucking-bugs attack on cacao plantation. By the implementation of pilot programs, training, demonstration, expanding networks, and making the Matang Ara Java as an area free from Helopeltis spp. The entire process of science and technology transfer is carried out with the pattern of education, training and assistance includes: socialization, training, and asistance for Matang Ara Jawa Farmers. The output of community service program at Matang Ara Jawa District is farmer understads of cocoa pod condomization, increase cocoa pod production with good quality and quantity, increased income of farmers.